Comparison of the effects of four different cochlear implant electrodes on intra-cochlear pressure in a model. (4th March 2017) - Todt, Ingo; Mittmann, Marlene; Ernst, Arneborg; Mittmann, Philipp
Abstract: Conclusion: Based on this model experiment, a small tip and low volume electrode show lowest intra-cochlear pressure values. Insertional support by a tool minimizes fast pressure changes. Higher electrodes volumes affect slow and fast pressure changes as well. Objective: Insertion causing low intra-cochlear pressure is assumed to be important for atraumatic cochlear implant surgery to preserve residual hearing. Cochlear implant electrodes differ in terms of parameters like tip size, length, volume, and technique of insertion. The aim of this study was to observe the effect of different cochlear implant electrodes on insertional intra-cochlear pressure in a cochlear model. Materials and methods: Cochlear implant electrode insertions were performed in an artificial cochlear model and intra-cochlear pressure changes were recorded in parallel with a micro-pressure sensor positioned in the apical region of the cochlear model to follow the maximum values, temporal changes, maximum amplitude, and frequency of changes in intra-cochlear pressure. Insertions were performed with four different electrodes (Advanced Bionics 1j, Helix, HFMS, and LW23). Results: This study found statistically significant differences in the occurrence of initial maximum pressure values correlating with the electrode tip size. The different electrodes and the technique of insertion significantly affected the occurrence of maximum value, amplitude, and frequency of intra-cochlear pressure occurrence.